2008
DOI: 10.1002/cncr.23687
|View full text |Cite
|
Sign up to set email alerts
|

Triplet combination of gemcitabine, paclitaxel, and carboplatin followed by maintenance 5‐fluorouracil and folinic acid in patients with metastatic nasopharyngeal carcinoma

Abstract: Objective: To evaluate the association between diagnosis of Parkinson disease (PD) and risk factors or early symptoms amenable to population‐based screening. Methods: A systematic review and meta‐analysis of risk factors for PD. Results: The strongest associations with later diagnosis of PD were found for having a first‐degree or any relative with PD (odds ratio [OR], 3.23; 95% confidence interval [CI], 2.65–3.93 and OR, 4.45; 95% CI, 3.39–5.83) or any relative with tremor (OR, 2.74; 95% CI, 2.10–3.57), consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 74 publications
(47 reference statements)
1
39
1
Order By: Relevance
“…5,6 The first study was a single-arm phase 2 open-label study that enrolled 32 patients with locally recurrent or metastatic NPC who have not received previous palliative chemotherapy to a first-line chemotherapy regimen consisting of six cycles of PGC. 5 When published in 2005, the study reported the highest response rates and OS rates achieved for metastatic NPC at the time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The first study was a single-arm phase 2 open-label study that enrolled 32 patients with locally recurrent or metastatic NPC who have not received previous palliative chemotherapy to a first-line chemotherapy regimen consisting of six cycles of PGC. 5 When published in 2005, the study reported the highest response rates and OS rates achieved for metastatic NPC at the time.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no standard of care for patients with metastatic disease, 4 the combination of gemcitabine, carboplatin, and paclitaxel chemotherapy generates one of the highest response and OS rates among palliative regimen. 5,6 Up to date, targeted agents have not been shown to significantly improve clinical outcomes, 7,8,9 and their role in the treatment of NPC currently remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, aggressive treatments for patients with a poorer prognosis are necessary. Chemotherapy remains the main therapeutic approach for metastatic NPC, with a number of reports confirming of its efficacy (Siu et al, 1998;Leong et al, 2008;Chen et al, 2013). However, the median survival was short, and there was no randomized study that compared palliative chemotherapy versus other palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the role of chemotherapy is well established for Jia-Xin Li 1, 2 , Shao-Min Huang 1 , Bi-Xiu Wen 2 , Tai-Xiang Lu 1 * metastatic NPC, but the objective response is still far from satisfied (Ngan et al, 2002;Chan et al, 2005;Leong et al, 2008). As NPC is highly sensitive to both chemotherapy and radiotherapy, whether local palliative radiotherapy for nasopharynx and metastatic tumors will provide additive value for overall survival when micro metastases are under control is a question worthy of consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is one of the widely used chemotherapeutic agents against many types of human cancers, 3,4 and has also been used for advanced NPC. [5][6][7][8] Although patients with advanced NPC benefit from paclitaxel-based combined chemotherapy, treatment failure often occurs due to development of acquired paclitaxel resistance. Thus, it is important to understand the underlying molecular mechanisms responsible for the development of paclitaxel resistance in NPC cells.…”
Section: Introductionmentioning
confidence: 99%